Malate initiates a proton-sensing pathway essential for pH regulation of inflammation - Yu-jia-nan Chen; Rong-chen Shi; Yuan-cai Xiang; Li Fan; Hong Tang; Gang He; Mei Zhou; Xin-zhe Feng; Jin-dong Tan; Pan Huang; Xiao Ye; Kun Zhao; et al. (Signal Transduction and Targeted Therapy)
Abstract Metabolites can double as a signaling modality that initiates physiological adaptations. Metabolism, a chemical language encoding biological information, has been recognized as a powerful principle directing inflammatory responses. Cytosolic pH is a regulator of inflammatory response in macrophages. Here, we found that L-malate exerts anti-inflammatory effect via BiP-IRF2BP2 signaling, which is a sensor of cytosolic pH in macrophages. First, L-malate, a TCA intermediate upregulated in pro-inflammatory macrophages, was identified as a potent anti-inflammatory metabolite through initial screening. Subsequent screening with DARTS and MS led to the isolation of L-malate-BiP binding. Further screening through protein‒protein interaction microarrays identified a L-malate-restrained coupling of BiP with IRF2BP2, a known anti-inflammatory protein. Interestingly, pH reduction, which promotes carboxyl protonation of L-malate, facilitates L-malate and carboxylate analogues such as succinate to bind BiP, and disrupt BiP-IRF2BP2 interaction in a carboxyl-dependent manner. Both L-malate and acidification inhibit BiP-IRF2BP2 interaction, and protect IRF2BP2 from BiP-driven degradation in macrophages. Furthermore, both in vitro and in vivo, BiP-IRF2BP2 signal is required for effects of both L-malate and pH on inflammatory responses. These findings reveal a previously unrecognized, proton/carboxylate dual sensing pathway wherein pH and L-malate regulate inflammatory responses, indicating the role of certain carboxylate metabolites as adaptors in the proton biosensing by interactions between macromolecules.